Validation of confocal laser endomicroscopy features of bladder cancer: The next step towards real-time histologic grading - Liem, Esmée I.M.L.; Freund, Jan Erik; Savci-Heijink, Cemile Dilara; Delarosette, Johan Joseph Maria; Kamphuis, Guido Maarten; Baard, Joyce; Liao, Joseph C.; van Leeuwen, Ton G.J.M.; De Reijke, Theo M.M.; De Bruin, Daniël Martijn (Elsevier, 2020)
Confocal laser endomicroscopy (CLE) is an optical imaging technique that allows for real-time in vivo microscopic imaging of bladder tissue. In this first validation of CLE features, we confirm that the proposed CLE features suffice for real-time tumour grading.Background: Cystoscopy enables the visualisation of suspicious bladder lesions but lacks the ability to provide real-time histopathologic information. Confocal laser endomicroscopy (CLE) is a probe-based optical technique that can provide real-time microscopic images. This high-resolution optical imaging technique may enable real-time tumour grading during cystoscopy. Objective: To validate and adapt CLE criteria for bladder cancer diagnosis and grading. Design, setting, and participants: Prospectively, 73 patients scheduled for transurethral resection of bladder tumour(s) were included. CLE imaging was performed intraoperatively prior to en bloc resection. Histopathology was the reference standard for comparison. Intervention: Cystoscopic CLE imaging. Outcome measurements and statistical analysis: Three independent observers evaluated the CLE images to classify tumours as low- or high-grade urothelial carcinoma (UC), or benign lesions. Interobserver agreement was calculated with Fleiss kappa analysis and diagnostic accuracy with 2 × 2 tables. Results and limitations: Histopathology of 66 lesions (53 patients) revealed 25 low-grade UCs, 27 high-grade UCs, and 14 benign lesions. For low-grade UC, most common features were papillary configuration (100%), distinct cell borders (81%), presence of fibrovascular stalks (79%), cohesiveness of cells (77%), organised cell pattern (76%), and monomorphic cells (67%). A concordance between CLE-based classification and histopathology was found in 19 cases (76%). For high-grade UC, pleomorphic cells (77%), indistinct cell borders (77%), papillary configuration (67%), and disorganised cell pattern (60%) were the most common features. A concordance with histopathology was found in 19 cases (70%). In benign lesions, the most prevalent features were disorganised cell pattern (57%) and pleomorphic cells (52%), and a concordance with histopathology was found in four cases (29%). Conclusions: The CLE criteria enable identification of UC. CLE features correlate to histopathologic features that may enable real-time tumour grading. However, flat lesions remain difficult to classify. Patient summary: Confocal laser endomicroscopy may enable real-time cancer differentiation during cystoscopy, which is important for prognosis and disease management.
Keywords: Bladder Cancer Grading; Confocal Laser Endomicroscopy; Non–Muscle-İnvasive Bladder Carcinoma; Sensitivity; Specificity; Urothelial carcinoma